2020
DOI: 10.3390/jrfm13110281
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Risk Management: A Literature Review and Agenda for Future Research

Abstract: The Enterprise Risk Management (ERM) process has heterogeneously developed across the world, although it represents a leading paradigm, supporting organizations to identify, evaluate, and manage risks at the enterprise level. Academics have studied the process, but there is no complete picture of the determinants and implications of such an integrated risk management process. Therefore, we present a systematic empirical literature review on ERM, based on a research protocol. The review highlights that the ERM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 101 publications
1
57
0
Order By: Relevance
“…For this reason, it is necessary to put in place a risk management plan, which is a set of activities, methodologies and coordinated resources focused on identifying possible internal and external risks that may affect the company, in order to take the necessary measures and ensure its safety and integrity (Anderson 2013 ). This process of planning, organizing, managing and controlling a company's activities to minimize the effects of risk on capital and profits is often called Enterprise Risk Management (ERM), (Anton et al 2020 ). Many scholars and practitioners have different views on risk classification systems and what types of risk to include or not in the ERM.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For this reason, it is necessary to put in place a risk management plan, which is a set of activities, methodologies and coordinated resources focused on identifying possible internal and external risks that may affect the company, in order to take the necessary measures and ensure its safety and integrity (Anderson 2013 ). This process of planning, organizing, managing and controlling a company's activities to minimize the effects of risk on capital and profits is often called Enterprise Risk Management (ERM), (Anton et al 2020 ). Many scholars and practitioners have different views on risk classification systems and what types of risk to include or not in the ERM.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…. This holistic approach of the ERM is widely discussed in the scientific literature, several reviews present this topic in detail CCOSO (2004), Gates (2006), Gordon et al (2009), Ching and Colombo (2014), Bromiley et al (2015), Fraser et al (2015), Wu et al (2015), Lackovic (2017), and more recently Anton and Nucu (2020), Kerraous (2020). The holistic approach to managing risk can enable organizations to deal with risks and opportunities more effectively, enhancing the organization's capability to create and preserve value for stakeholders (CCOSO 2004).…”
Section: Erm Vs Traditional Risk Managementmentioning
confidence: 99%
“…A recent review based on a large sample from 2008-2019 literature indexed on the ISI Web of Science has revealed that the most frequently investigated topic of ERM is firm performance. (Anton and Nucu 2020).…”
Section: Erm Vs Traditional Risk Managementmentioning
confidence: 99%
“…Many studies conducted by previous researchers were related to ERM, such as (Ahmed and Manab, 2016); (Mohd-Sanusi et al, 2017); (Waseem-Ul-Hameed et al, 2017); (Lundqvist and Vilhelmsson, 2018); (Mahmod et al, 2018); (Lechner & Gatzert, 2018); (Bohnert et al, 2019); and (Anton & Nucu, 2020), highlight the factors in ERM adoption and implementation which include personnel perceptions of risk management and the need for a risk awareness culture at all organizational levels before adopting ERM. Oliveira et al (2019), identified ten critical factors that can influence the successful implementation of ERM in an organization.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative industrial risks arise due to uncoordinated and balanced innovative projects, which are accompanied by the emergence of various stochastic effects that have an impact on innovative processes of complex economic systems (Ponikarova & kadeeva, 2020). Implementation ERM is most important for various sectors, banks, insurance and non-financial companies, especially SMEs (Anton & Nucu, 2020). Other studies on the relationship between risk management and balanced scorecard in service banks (Elkhouly et al, 2015); and (Ratri & Pangeran, 2020).…”
Section: Introductionmentioning
confidence: 99%